Penentuan Kriteria Performansi pada Eksternal Fiksator Berbasis Hexapod Menggunakan Delphi dan Analytical Hierarchy Process (AHP) - Durkes Herlina Apriani; Ilham Priadythama; Lobes Herdiman (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2019)
An external fixator is a medical device to support bones that require correction due to a defect or fracture. An external fixator with a hexapod system is the right device for correction of complex deformities because of its ability to repair bone in three dimensions. There are many external hexapod fixator products that are sold commercially with varied designs. So far, the success rate of fixators has only been reviewed from the final results on bone correction and frame specifications for biomechanical testing. This study aims to determine the criteria for an external fixator and determine the level of importance between the criteria. Determination of criteria and ranking of interests is carried out by Delphi and Analytical Hierarchy Process (AHP). The results of this study indicate that there are four main criteria for external fixators for each criterion assessment. The benefit of this research is to further develop hexapod based external fixator products.